The grieving process at school. Prevention, assessment and intervention. (Journal of Parents and Teachers, 2015)
The article exposes the need for the psychological care of children in mourning in the education context that is a fully planned and programmed process, within a global perspective: educational, pedagogical and psychological. Also it is briefly presented some guidance for the work of prevention, assessment and intervention with mourning students.
Keywords: Grief; Education; Children; Psychological Intervention; Educational Guidance; tea editions